SELF-EFFICACY AND INDONESIAN JUNIOR HIGH SCHOOL STUDENTS’ READING ABILITY IN ONLINE CLASSES - Anne Yustica Pramesti Sumarsono; Concilianus Laos Mbato (Widya Mandala Surabaya Catholic University, 2022)
Self-efficacy in reading is considered to be the cause and result of academic achievement, especially in online learning where students need to learn independently. In this study, the researchers attempted to find out the impacts of self-efficacy on the reading ability of 9th-grade students at SMP 5 Purwokerto during online learning. There were 32 students from class 9A who participated in this study. The research question was: What is the perceived effect of self-efficacy on the reading ability of 9th-grade students at SMP 5 Purwokerto? The researchers used the qualitative method with two research instruments. The results reveal that 9th-grade students have a high level of self-efficacy, can find solutions to every problem, and read a lot of new things from the internet, newspapers, novels, or magazines. Online classes, therefore, bring students’ independence to find solutions from the problems. This study contributes to learning English on reading skills during online school.